2020
DOI: 10.3390/resources9060072
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Current State of Knowledge in the Field of Waste Heat Recovery in Sewage Systems

Abstract: The need for efficient use of energy and sustainable energy management and the fact that large quantities of heat are deposited in the discharged sewage have contributed to the development of research on waste heat recovery. Gray water began to be seen not just as waste, but also as an alternative source of energy. Research related to the development, improvement, and finally, the popularization of waste energy recovery devices and systems has evolved rapidly over the last two decades. Initially, technologies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
9
0
1
Order By: Relevance
“…Research shows that if the recovered energy is used to preheat water in a residential building, the return on investment can be achieved after only two years [20]. However, much depends on the type of building [21], the tap fittings used [22], the method for recovering the heat deposited in the drain water [23], and the price of the primary energy source [24]. The amount of drain water used as a heat source is also important.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that if the recovered energy is used to preheat water in a residential building, the return on investment can be achieved after only two years [20]. However, much depends on the type of building [21], the tap fittings used [22], the method for recovering the heat deposited in the drain water [23], and the price of the primary energy source [24]. The amount of drain water used as a heat source is also important.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, heat could potentially also be extracted from different types of wastewater. Indicative examples that can be found in the literature concern the exploitation of: (i) the wastewater ingress within an underground transport line [18]; (ii) wastewater from livestock and agricultural farms [19]; (iii) sewer wastewater [20]; (iv) wastewater from showers [21]; and other applications involving wastewater and heat-exchanging potential.…”
Section: Whr Technologiesmentioning
confidence: 99%
“…These are devices whose task is to transfer the waste heat deposited in the shower drain water to the tap water flowing into the shower system [60]. Depending on the method of conducting installations and the availability of space for the installation of a heat recovery system, vertical and horizontal heat exchangers as well as devices installed under the floor shower drain can be used [61]. The water preheated in the heat exchanger can be led to the domestic hot water heater and/or directly to the shower mixing valve [62].…”
Section: Shower Heat Exchangersmentioning
confidence: 99%
“…The research showed that only about 30% of the respondents have space in their dwellings to install a vertical heat exchanger, with the answer "definitely yes" indicated by only 23% of them (Q37). As is well known, it is these devices that are most effective and are most often used [61]. The use of devices with a different design results in a reduction of the amount of recovered heat.…”
Section: The Use Of Shower Heat Exchangersmentioning
confidence: 99%